Pendidikan Kesehatan Berbasis Video terhadap Pengetahuan dan Kepatuhan Minum Obat Penderita Diabetes Melitus di Samarinda - Bernadetha Bernadetha; Joko Sapto Pramono; Yona Palin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Diabetes mellitus continues to be a major global health challenge due to its high prevalence and steady increase in cases. Effective management of DM can be achieved by strengthening self-care, primarily through improved knowledge. Health promotion has a vital role in enhancing awareness and disease management, particularly when delivered through video media that is visually engaging and aligned with technological progress. This study aimed to examine the impact of health education using video media in the Samarinda local language on the knowledge of DM patients at Baqa Health Center. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed, involving 52 participants recruited through consecutive sampling who met the inclusion criteria. Data were obtained using the DKQ-24 (Diabetes Knowledge Questionnaire) consisting of 24 items. The Wilcoxon statistical test was applied with a significance level of α = 0.05. Findings revealed that the mean score prior to the intervention was 1.21, which rose to 2.54 following the intervention (ρ = 0.000). The significant increase demonstrates that health promotion through videos in the Samarinda dialect is highly effective in improving knowledge among DM patients at Baqa Health Center.